Dynamics of Ninhydrin‐Reactive Nitrogen and pH in Gravesoil During the Extended Postmortem Interval1. Issue 5 (23rd July 2013) - Anderson, Brianna; Meyer, Jessica; Carter, David O.
Abstract: Estimating the postmortem interval of skeletal remains is difficult, as few tools exist to do so. To address this problem, we conducted a field experiment to measure the chemistry of swine ( Sus scrofa domesticus Linnaeus) gravesoil after 1 year and 3 years postmortem. Carcasses were placed on the soil surface of a pasture during June in a cold (Dfa) climate. Significant ( p  < 0.05) increases in ninhydrin‐reactive nitrogen, pH, total nitrogen, and nitrate in gravesoil were detected 1 year postmortem. Significant differences in gravesoil chemistry were not detected 3 years postmortem. These observations coincided with gaps in plant growth 1 year postmortem and the development of lush vegetation 3 years postmortem. We conclude that these phenomena can be used to assist the decision‐making process regarding the allocation of resources during the early stages of a death investigation.